Para além de meninas estupradas, sobreviventes: a incidência da Lei Maria da Penha aos casos de estupro de vulnerável intrafamiliar contra meninas tramitados no TJPA - SODRÉ, Laura Ribeiro Silva (2024)
This work seeks to analyze the extent to which the crime of intrafamilial vulnerable rape against girls is understood by judges as gender-based violence capable of attracting the applicability of the Maria da Penha Law to criminal proceedings in the Court of Justice of the State of Pará (TJPA). Through feminist and criminological theoretical frameworks on rape, it analyzes court rulings involving vulnerable rape judged by the TJPA between 2021 and 2024. Based on this direction, this monograph is divided into three chapters that reflect the paths explored throughout this research. In the first chapter, gender violence within the Maria da Penha Law is addressed, establishing the theoretical framework for the research. Next, the concept of "gender" in feminist literature is examined, focusing on the gendering of violence against women. The analysis proceeds with an intersectional approach to violence and the process of creating the Maria da Penha Law as a protective mechanism, including the role of feminist movements in Brazil. Finally, the term “gender-based violence” is examined as a criterion for the competence of the Domestic and Family Violence Court against Women. In the second chapter, the fundamental categories of feminism are revisited to analyze rape as an instrument of power, contextualized in light of criminology and feminist perspectives. The analysis emphasizes cases of vulnerable rape against girls, incorporating data on child sexual violence, in dialogue with theoretical references. Finally, the theoretical contributions are applied to statistics on vulnerable rape in the State of Pará. In the third chapter, examples of rulings from the Court of Justice of the State of Pará (TJPA) will be presented and analyzed concerning intrafamilial vulnerable rape cases against girls and the incidence of the Maria da Penha Law and Domestic and Family Violence Courts (JVDFM). Subsequently, the consequences of the judges' interpretations of the crime in question will be analyzed. Through this journey, the work demonstrates the absence of a theoretical framework regarding the gender category in the judges' discourses by failing to interpret intrafamilial vulnerable rape against girls as a manifestation of gender-based violence against women. In conclusion, this work highlights the detrimental consequences of jurisdictional conflict for survivors of rape and demonstrates that intrafamilial sexual violence against girls should be presumed as a form of gender-based violence, based on theoretical references and national and international legislation.